PERSEPSI SISWA TERHADAP PEMBELAJARAN MATEMATIKA SECARA DARING MENGGUNAKAN APLIKASI CLASS ROOM DALAM MASA PANDEMI COVID-19 - Mira Sara Samaran; Yoseph Batkunde; Olivir Srue (Mandalika Mathematics and Educations Journal, 2022)
The purpose of this study was to determine students' perceptions of online mathematics learning using the classroom application during the COVID-19 pandemic in class VIII students of SMP. Subjects taken for this study amounted to 7 students and 1 teacher of mathematics. Data collection techniques were carried out with observation and interview guidelines. Data analysis techniques used are reducing data, presenting data, and drawing conclusions. The result obtained is that students' perceptions of online learning in mathematics subjects during the Covid-19 pandemic have a negative perception of online learning of mathematics subject matter. This is because the majority of students do not understand the online learning material that is delivered, how to deliver math material which is considered less attractive, as well as student opinions about online learning which is considered less effective, and students feel unhelpful and hinder in accepting the online learning system.